2015
DOI: 10.3332/ecancer.2015.542
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcaemia with disseminated osteolytic lesions: a rare presentation of childhood acute lymphoblastic leukaemia

Abstract: Acute lymphoblastic leukaemia (ALL) presenting with hypercalcaemia and lytic bone lesions is a rare event in children unlike adults. We report a 15-year-old boy with acute lymphoblastic leukaemia and hypercalcaemia. He had normal peripheral blood count and the peripheral smear did not show blast. The bone marrow examination revealed Pre B ALL phenotype with aberrant expression of CD13. The skeletal survey showed osteolytic lesions. Hypercalcaemia was treated with zoledronic acid. He attained remission only aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…Only 2 case reports (11.5-and 15-year-old boys) have been found in English literature about ZA use in hypercalcemia of children with the diagnosis of ALL. 20,21 Hypercalcemia was diagnosed at the time of initial diagnosis of ALL in both cases, whereas it was developed during relapse in our case. ZA had been successfully used as a first-line agent in the treatment of hypercalcemia in both cases.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Only 2 case reports (11.5-and 15-year-old boys) have been found in English literature about ZA use in hypercalcemia of children with the diagnosis of ALL. 20,21 Hypercalcemia was diagnosed at the time of initial diagnosis of ALL in both cases, whereas it was developed during relapse in our case. ZA had been successfully used as a first-line agent in the treatment of hypercalcemia in both cases.…”
Section: Discussionmentioning
confidence: 56%
“…ZA had been successfully used as a first-line agent in the treatment of hypercalcemia in both cases. 20,21 In contrast, pamidronate was used as a first-line treatment agent in our case, because ZA was unavailable in our clinic despite it being a more potent agent than pamidronate. 22 In addition, calcium normalization has been reported at the fourth day of ZA administration in a study on adults with malignancy-associated hypercalcemia.…”
Section: Discussionmentioning
confidence: 96%
“…Shimonodan et al [9] revealed the fact that elevated PTHrPs in ALL come from lymphoblasts, associated with its frequent relapses and poor prognosis. Additionally, other leukemic blasts-producing cytokines including transforming growth factor-α, tumor necrosis factor, interleukin-1, and prostaglandin E2 may affect these phenomena [10]. Although leukemic infiltration of the kidney is usually asymptomatic, it can lead to bilateral renal enlargement, acute kidney injury (AKI), or secondary hypertension [11].…”
Section: Discussionmentioning
confidence: 99%
“…Há controvérsias sobre a mudança do prognóstico relacionado com a presença de lesões osteolíticas e hipercalcemia em pacientes com LLA. Alguns estudos sugerem que não existe relação entre a presença das lesões e o pior prognóstico de pacientes com LLA 9,12,19,20 . Há evidência na literatura de que o período de remissão da doença é reduzido em pacientes com lesões osteolíticas 11 .…”
Section: -5unclassified